p53, SKP2, and DKK3 as MYCN Target Genes and Their Potential Therapeutic Significance - Chen, Lindi; Tweddle, Deborah A. (Frontiers in Oncology, 2012)
Neuroblastoma is the most common extracranial solid tumour of childhood. Despite significant advances, it currently still remains one of the most difficult childhood cancers to cure, with less than 40% of patients with high-risk disease being long-term survivors. MYCN is a proto-oncogene implicated to be directly involved in neuroblastoma development. Amplification of MYCN is associated with rapid tumour progression and poor prognosis. Novel therapeutic strategies which can improve the survival rates whilst reducing the toxicity in these patients are therefore required. Here we discuss genes regulated by MYCN in neuroblastoma, with particular reference to p53, SKP2 and DKK3 and strategies that may be employed to target them.